Comparison of Load-Bearing Capacities of 3-Unit Fiber-Reinforced Composite Adhesive Bridges with Different Framework Designs - Tacir IH; Dirihan RS; Polat ZS; Salman GO; Vallittu P; Lassila L; Ayna E (INT SCIENTIFIC LITERATURE, INC, 2022)
Background: The aim of this study was to investigate and compare the load-bearing capacities of three-unit direct resin-bonded fiber-reinforced composite fixed dental prosthesis with different framework designs.Material/Methods: Sixty mandibular premolar and molar teeth without caries were collected and direct glass fiber-resin fixed FDPs were divided into 6 groups (n=10). Each group was restored via direct technique with different designs. In Group 1, the inlay-retained bridges formed 2 unidirectional FRC frameworks and pontic-reinforced transversal FRC. In Group 2, the inlay-retained bridges were supported by unidirectional lingual and occlusal FRC frameworks. Group 3, had buccal and lingual unidirectional FRC frameworks without the inlay cavities. Group 4 had reinforced inlay cavities and buccal-lingual FRC with unidirectional FRC frameworks. Group 5, had a circular form of fiber reinforcement around cusps in addition to buccal-lingual FRC frameworks. Group 6 had a circular form of fiber reinforcement around cusps with 2 bidirectional FRC frameworks into inlay cavities. All groups were loaded until final fracture using a universal testing machine at a crosshead speed of 1 mm/min.Results: Mean values of the groups were determined with ANOVA and Tukey HSD. When all data were evaluated, Group 6 had the highest load-bearing capacities and revealed significant differences from Group 3 and Group 4. Group 6 had the highest strain (p>0.05). When the fracture patterns were investigated, Group 6 had the durability to sustain fracture propagation within the restoration.Conclusions: The efficiency of fiber reinforcement of the restorations alters not only the amount of fiber, but also the design of the restoration with fibers.